Analisis Kecemasan Siswa pada Pembelajaran Matematika Berbasis Problem Based Learning di SMP Negeri 3 Kota Jambi - Dewi, Sri; Simamora, Risma (Jurnal Ilmiah Dikdaya, 2022)
Mathematics anxiety is a feeling of pressure and nervousness that interferes with manipulating numbers and solving mathematical problems, both in everyday life and in the learning process. This study aims to describe the level of student anxiety in learning mathematics based on problem based learning at SMP Negeri 3 Jambi City. The subjects of this study were students of class VIII SMP Negeri 3 Jambi City, consisting of 4 classes. Each class is taken by 10 student representatives based on the 5 highest knowledge and 5 lowest knowledge. The data collection technique is by distributing questionnaires to all students who have been selected as many as 40 students. Researchers distributed questionnaires to get results/data on anxiety levels of SMP Negeri 3 Jambi City students. The researcher also conducted interviews with 8 student representatives to strengthen the research data. The results of this study indicate that the highest aspect of the student anxiety variable is the "fear" aspect which has an average of 1.54 (medium). Overall, the results of the anxiety level of students in SMP Negeri 3 Jambi City class VIII belong to the category of mild anxiety level with an average value percentage of 1.25 indicating that the level of anxiety of students in learning mathematics is mild anxiety. Anxiety is one of the reasons why proper interpersonal relationships are so important in understanding mathematics. This is because anxiety itself can increase, is subjective, and can make it difficult for students to understand. Students are still carried away by their unpleasant past experiences related to mathematics. Usually students who are more anxious will try harder, but their understanding will deteriorate further, making them even more anxious. Therefore, students will learn partially, this will form students' interpersonal experiences. Students who feel less anxious in learning mathematics because the student knows that he is able to solve problems in learning mathematics, then he will be able to use his anxiety in solving the problem.